Synthesis of damage-tolerant Cu-matrix composites with nacre-inspired laminate-reticular hierarchical architecture via tuning compositional wettability. (September 2020) - Hu, Zhi-Jie; Guo, Rui-Fen; Chen, Shuo-Ming; Jin, Quan; Shen, Ping
Abstract: We constructed a nacre-inspired laminate-reticular hierarchical architecture in Cu/(TiC−Cr3 C2 ) composites by tuning the wettability between loose freeze-cast ceramic lamellae and Cu melt. This unique architecture takes full advantage of superb intrinsic strength of the ceramic particles and toughness of the metal, stimulating multiple extrinsic toughening mechanisms such as synergistic deformation of the metal and ceramic layers, ductile-ligament bridging and multi-cracking mode. As a consequence, the resultant composites containing 30 vol% ceramics exhibited exceptional damage-tolerant properties with a fracture toughness of 62.6 ± 1.0 MPa⋅m 1/2 and a bending strength of 639 ± 27 MPa. Graphical abstract: Image, graphical abstract